2019
DOI: 10.1103/physrevlett.123.237001
|View full text |Cite
|
Sign up to set email alerts
|

Chiral Higgs Mode in Nematic Superconductors

Abstract: Nematic superconductivity with spontaneously broken rotation symmetry has recently been reported in doped topological insulators, M x Bi 2 Se 3 (M=Cu, Sr, Nb). Here we show that the electromagnetic (EM) response of these compounds provides a spectroscopy for bosonic excitations that reflect the pairing channel and the broken symmetries of the ground state. Using quasiclassical Keldysh theory, we find two characteristic bosonic modes in nematic superconductors: the nematicity mode and the chiral Higgs mode. The… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(14 citation statements)
references
References 59 publications
2
12
0
Order By: Relevance
“…The lack of change of the Knight shift below T c for all angles (Fig. 9) as contrary to what found in the nematic phase 16 is consistent with existing theory that the dvector for the chiral phase would be pointing to the c-axis 42 . Thus, our finding suggests that superconductors with strong spin-orbital interaction 14 is a land much more fertile than we thought.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…The lack of change of the Knight shift below T c for all angles (Fig. 9) as contrary to what found in the nematic phase 16 is consistent with existing theory that the dvector for the chiral phase would be pointing to the c-axis 42 . Thus, our finding suggests that superconductors with strong spin-orbital interaction 14 is a land much more fertile than we thought.…”
Section: Discussionsupporting
confidence: 90%
“…One of the crucial parameters important for selecting between the two states is the Fermi surface shape. It has been theoretically shown by several groups that the chiral state can be stabilized when the Fermi surface becomes more two-dimensional [42][43][44] . Experimentally, photoemission and quantum oscillation measurements have suggested that the Fermi surface becomes more two-dimensional as carrier density increases 45,46 .…”
Section: Discussionmentioning
confidence: 99%
“…However, there are several issues unresolved; in particular, apparent inconsistency in the nematic direction and its relation to the possibly existing in-plane symmetry-breaking field are most important subjects to be investigated next. Also, predicted novel phenomena originating from nematic superconductivity, such as the superconductivity-fluctuation-induced nematic order above T c [105], the chiral Higgs mode in the electromagnetic response [106], spin polarization of Majorana quasiparticles in a vortex core [107], and nematic Skyrmion texture near half-quantum vortices [108], would be worth seeking for.…”
Section: Summary and Perspectivesmentioning
confidence: 99%
“…The kernel of the matrix in Eq. ( 54) gives the eigenfrequencies of bosonic excitations, ω C Γ (q) (Γ = D, E), and the damping rates of each mode [100]. The right-hand side of Eq.…”
Section: Excitation Of the Collective Modes By The Acoustic Wavesmentioning
confidence: 99%